Differences in attitude towards end-of-life care among haemodialysis patients and their family members in two Malaysian hospitals - Azahar, Aizad; Ibrahim, Noor Airini; Kharuddin, Ahmad Thariq (International Islamic University Malaysia, 2021)
INTRODUCTION: End-of-life (EOL) care has become an important topic of discussion in those with chronic illness, especially in End Stage Renal Disease (ESRD) patients on dialysis. This study explored attitudes towards the EOL care among haemodialysis patients and compared them with the patients’ family members. MATERIALS AND METHODS:The study was a cross-sectional descriptive study conducted in two tertiary hospitals in Malaysia. The data was collected by using a survey questionnaire from 164 participants which consisted of 82 pairs of patients and their relatives. RESULTS:‘Patient’ and ‘family’ groups demonstrated differences in their preferences regarding EOL care options. Family members group favoured cardiopulmonary resuscitation (81.7% vs 41.4%) (p <0.001), endotracheal intubation (80.5% vs 43.9%) (p = 0.989) and nasogastric tube feeding (87.8% vs 67%) (p = 0.001) more than patients themselves. The physician was the most nominated surrogate decision-maker by the patient (91.5%). Majority of the patients (57.3%) felt uncomfortable discussing EOL care options. There was significant correlation between duration of dialysis and patients’ EOL preferences where patients less than 5 years on haemodialysis favoured CPR (55.9% vs 31.3%; p = 0.026), intubation (55.9% vs 35.4%) and nasogastric tube feeding (82.3% vs 56.3%; p = 0.013) compared to patients who had been on haemodialysis for 5 years or longer. CONCLUSION:This study demonstrated significant differences between the attitudes of the patients and their relatives regarding EOL care preferences.